Design of a Village Letter C Information System Based on a Website Using Apps Script - Ma’munuddin; Sri Mulyati (International Journal Software Engineering and Computer Science (IJSECS), 2024)
In terms of data management administration, recording land ownership documents such as Letter C is one of the areas that uses information systems in the village in its implementation, but many villages still rely on manual recording methods, causing operational inefficiencies and minimizing the risk of data loss. With the need for a less complicated process, the purpose of this study is to create and develop a web-based Letter C information system application using Google Apps Script that is digital and integrated to simplify land ownership management and data. One of the development-oriented approaches used is Prototyping. Able to create a working model of the system in its most primitive form and to get initial feedback from users. This allows the system to develop iteratively driven by user needs and preferences. This leads to a system that can record, search, and update land ownership data dynamically. The results of the study show that the proposed Letter C data management system greatly improves the efficiency of Letter C data management while reducing the risk of data loss or making errors. The implication of implementing this system is the increased ability of the village government to provide structured, transparent, and accountable land ownership administration services. This in turn can enable a more accurate and data-based decision-making process in the management of village land assets. Thus, this research can be part of the efforts to digitize the village governance system in the early period, especially in land data management